Samarthāñcẽ sāmārthya, kĩvā, Śrīrāmadāsa Svāmīñcā līlānugraha - Āṭhalye, Krshṇājī Nārāyaṇa, 1852-1927 (SAMP early 20th-century Indian books project ;, 1925)
On the life and works of Rāmadāsa, b. 1608, Marathi religious poet and founder of Samartha Sampradaya.